Substitution Box Design Based From Symmetric Group Composition - Muhammad Fahim Roslan; Kamaruzzaman Seman; Azni Haslizan Ab Halim; M. Norazizi Sham Mohd Sayuti (IOP Publishing Ltd, 2024)
Indexed by SCOPUS/ERA